An experimental study of the structural capacity of composite beam (concrete cast c-beam) - Muhammad Alif Asyraf, Hairon Anuar (2017)
This study was conducted to determine the ultimate strength of a composite steel beam. The main objective of this study was to determine the ultimate load, deflection and the stress and strain value. In this study, three samples have been used to determine the average result that accurate for fulfilling the requirements of an experiment. Using composite beam in the industry can accelerate the time of a construction project because it is easy to handle and does not require the skills of an expert in the field of construction. Compressive strength test were conducted to ensure the characteristic strength of the concrete is achieve. Magnus frame test were conducted to determine ultimate structural capacity for composite beam in term of ultimate load, deflection, stress and strain. All the procedures are prepared accordingly, to assure the research objectives are applicable, and to secure proper sequence and smooth running of the entire flow, from start until end. The samples were prepared with same properties. All three samples of the composite beam have been cast at Heavy Structure Laboratory, University Malaysia Pahang (UMP) and compressive strength test also were conducted at same laboratory. The finding shows that the objectives of this study have been achieved. From compressive strength test, its shows the characteristic strength of the concrete have been used for this study is 23.95 Mpa which is nearly reached the required strength. From the magnus frame test, its shows the rectangular composite beam with size of 150 x 300 x 2000 mm can received load up to 113 kN. While the maximum deflection occurred among three samples only 7.42 mm. The result shows the load applied and the strain value of both material which are concrete and steel are related. Where the value of strain increase together with the increasing of load applied to the composite beam until it’s failed.